Enzymatic assay for conjugated bilirubin (Bc) in serum using bilirubin oxidase (BOD) - Kimura, Shigeki (J Clin Lab Anal, 1999)
We described an automated enzymatic assay for conjugated bilirubin (Bc) in serum using the Iatro D‐Bil kit, with bilirubin oxidase (EC 1.3.3.5 BOD) from Myrothecium species. The specificity of the enzyme in the Iatro D‐Bil kit was examined by analyzing unconjugated bilirubin (Bu), delta bilirubin (Bδ), and Bc with high‐performance liquid chromatography (HPLC), before and after the enzymatic reaction using BOD. The within‐assay coefficients of variation (CV) of this method were 0.58 to 5.00% (n = 20) at 1.4 to 155.8 μmol/L. Day‐to‐day Cvs ranged from 1.61 to 7.14% at 1.2 to 182.1 μmol/L. The analytical recovery was 96 to 101%. The presence of ascorbic acid, reduced glutathione, l‐cysteine, uric acid, urea, creatinine, glucose, lipemic material, anticoagulants, hemoglobin, or human serum albumin did not affect this assay system. The correlation coefficient between values obtained with the Iatro D‐Bil kit (y) and HPLC method as reference for conjugated fractions (x) was; r = 0.983, y = 0.952x + 8.851 μmol/L, Sy/x = 11.97 (n = 56). We studied serum Bc levels, not including Bu and Bδ, in patients with hepatic diseases or autoimmune hemolytic anemia. Levels of Bc obtained by the proposed method changed more rapidly than did those of direct bilirubin (D‐Bil) obtained by diazo‐dye method during the course of the diseases. J. Clin. Lab. Anal. 13:219–223, 1999. © 1999 Wiley‐Liss, Inc.